Spermatogonial stem cells and spermatogenesis in mice, monkeys and men - Fayomi, Adetunji P. (Stem Cell Res, 2018)
Continuous spermatogenesis in post-pubertal mammals is dependent on spermatogonial stem cells (SSCs), which balance self-renewing divisions that maintain stem cell pool with differentiating divisions that sustain continuous sperm production. Rodent stem and progenitor spermatogonia are described by their clonal arrangement in the seminiferous epithelium (e.g., A(single), A(paired) or A(aligned) spermatogonia), molecular markers (e.g., ID4, GFRA1, PLZF, SALL4 and others) and most importantly by their biological potential to produce and maintain spermatogenesis when transplanted into recipient testes. In contrast, stem cells in the testes of higher primates (nonhuman and human) are defined by description of their nuclear morphology and staining with hematoxylin as A(dark) and A(pale) spermatogonia. There is limited information about how dark and pale descriptions of nuclear morphology in higher primates correspond with clone size, molecular markers or transplant potential. Do the apparent differences in stem cells and spermatogenic lineage development between rodents and primates represent true biological differences or simply differences in the volume of research and the vocabulary that has developed over the past half century? This review will provide an overview of stem, progenitor and differentiating spermatogonia that support spermatogenesis; identifying parallels between rodents and primates where they exist as well as features unique to higher primates.